Advanced current and power consumption monitoring with overload protection / Dinie Haqeemy Abdul Mu'izz - Abdul Mu'izz, Dinie Haqeemy (2024)
In today's increasingly digitized and energy-conscious society, it is critical to correctly measure and analyze current and power usage while preventing overloads. To solve these difficulties, this proposal presents an improved monitoring and protection system that uses cutting-edge technologies. The system combines modern current and power monitoring devices with an intelligent overload protection mechanism. The monitoring devices use highly precise sensors and advanced algorithms to measure and analyze current and power consumption in real time. The acquired data is analyzed and presented in a user-friendly interface, allowing users to track and analyze their energy consumption habits. The system provides extensive insights into individual appliance usage as well as the system's overall energy profile. This information enables customers to make more educated decisions about energy usage optimization and efficiency enhancement. Furthermore, the project emphasizes the need for overload protection in preventing electrical equipment damage and ensuring the electrical system's safety. The system continuously monitors the load on the system and uses advanced algorithms detect and prevent overloads. In the event of an impending overload, the system takes appropriate precautions to reduce the danger, such as automatically shedding non-critical loads or warning the user to act. The proposed system stands out for its excellent precision, real-time monitoring, and intelligent overload protection. It provides a scalable system that may be used in a variety of environments, including residential, commercial, and industrial. This project intends to contribute to the sustainability and safety of modern electrical systems by enabling effective energy consumption monitoring and safeguarding against overload situations